A SPATIAL MODEL OF CHANGE OF FDI FIRM POPULATION IN ISTANBUL - Sevkiye Sence Turk; Lale Berkoz (European Regional Science Association (ERSA), 2005)
Within the context of the foreign capital- orientation programme having been implemented since 1980, the regulation concerning the foreign investments in Turkey were freed and this has paved the way for important developments in terms of the entrance of foreign capital into the country and foreign investments. As a result of this, there was a dramatic increase in number of foreign investment firms in Turkey and, especially, Istanbul. The increase in foreign investments had major impacts on the spatial transformation of Istanbul Metropolitan Area. In this paper, change in FDI firm population in Istanbul has been viewed between 1990- 2004. An explanatory model has been applied to determine causes factors affecting change at the district level. Foreign firms were generally in parallel with the development of CBD ( the central business district) of Istanbul and Foreign Capital firms in Istanbul appear to demonstrate a trend towards accumulating in CBD.
Keywords: 330